Development of METAFORA (Temperature and Heat Interactive Learning Media for Senior High School) Using Lectora Inspire 18 - Diana Ayu Aprilia; Alex Harijanto; Lailatul Nuraini (Jurnal Ilmiah Pendidikan Fisika, 2023)
This research aimed to develop physics interactive learning media (Lectora Inspire 18) based on temperature and heat. The development result was checked to determine the interactive learning media's validity, effectiveness, and students' responses. The research method uses Nieveen methods such as preliminary research, prototyping, and assessment phases. The interactive learning media were validated by 3 validators, including 2 expert validators and a user validator. Interactive learning media effectiveness and students' responses were analyzed by two trial activities (a limited trial including 10 students and a wide trial including 36 students). The development result is physics interactive learning media for senior high school (METAFORA) on heat and temperature, used with a PC and smartphone. Based on the evaluation of three validators, the validity score of interactive learning media is 4,74, and it is classified as valid. The N-Gain formula calculates interactive learning media from students' pre-test and post-test results. The interactive learning media effectiveness N-gain score is 0.60 (medium) based on a limited trial and 0.66 (medium) based on a large trial. The student's response was analyzed from the questionnaire given after implementing interactive learning media. In the limited trial, the student response percentage is 79.22%, which falls into the good category, and in the wide trial, it is 80.34 percent, which falls into the very good category. Based on the data analysis results, the physics interactive learning media Lectora Inspire 18 based on temperature and heat matter is valid, effective, and suitable as an alternative medium for physics learning.